Status of Serum Zinc Level in Hypothyroid Patients with Normal Serum Albumin Level: A Case Control Study - Regmi, Dipesh; Gautam, Narayan; Shahi, Aakash; Bohara, Sharad; Subedi, Seema; Jayan, Archana (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: Decreased thyroid hormone synthesis and low levels of circulating thyroid hormones result in clinical hypothyroidism causing many metabolic processes to slow down. Zinc is essential for many biochemical processes and cell proliferation. Thyroid hormones influence Zinc metabolism by affecting absorption and excretion. MATERIAL AND METHODS: This case-control study was conducted in subclinical hypothyroidism (n=30), overt hypothyroidism (n=30) and compared with age and sex matched euthyroid controls (n=30) attending UCMS-TH. Serum free T3 (fT3), free T4 (fT4) and Thyroid Stimulating Hormone (TSH) were estimated by ELISA. The serum Zinc and Albumin were estimated by colorimetric Nitro-PAPS and BCG dye binding method respectively. RESULTS: The overall frequency of Zinc deficiency has been observed 12 (40%) in overt hypothyroidism, 9 (30%) in subclinical hypothyroidism and two (6.66%) in euthyroid controls. A significant association between serum Zinc with fT3, fT4 levels (p=0.0046) and with TSH level (p-value=0.030) was observed in all cases. The positive correlation of serum Zinc with fT3 level (r=0.217, p=0.04), fT4 level (r=0.267, p=0.011) while serum negative correlation with TSH level (r=-0.234, p=0.026) and Albumin (r=-0.039, p=0.713) were observed. The odds ratio shows 9.33 times Zinc deficiency likely to occur in overt hypothyroidism (CI: 1.86-46.68; p-value=0.0065) whereas 6.0 times in subclinical hypothyroidism (CI:1.17- 30.72; p-value=0.0315) than euthyroid controls. CONCLUSION: The significant difference in Zinc deficiency was observed in overt hypothyroid patients. However, non-significant difference in sub-clinical hypothyroidism as compared to euthyroid controls was found in all groups having normal albumin level. This may conclude that with progression of hypothyroidism there is significant decrease in Zinc with normal albumin. Hence, there is association between thyroid profile and serum Zinc status.